Outcome Predictor of Spontaneous Supratentorial Intracerebral Hemorrhage Management - Touhidur Reza, Abul Hasan Md; Karim, Md Rabiul; Mohammad Humayun Rashid; Mohammad Sanaullah; Mahfujul Quader; Chowdhury, S M Noman Khaled; Tapas Sarker; Md Motasimul Hasan; Ansar Uddin Ahmed; Md Kamal Hossain (Bangladesh Journal of Neurosurgery, 2024)
Background: Spontaneous intracerebral hemorrhage (SICH) is responsible for higher morbidity and mortality rates than ischemic stroke. Although SICH is less common than ischemic stroke. Identifying the predictors of outcome after spontaneous supratentorial intracerebral hemorrhage is crucial for a clinical decision-making framework and implementing efficient therapeutic measures. Aims: The study aimed to analyze the clinical profile, assess the outcome, and identify the outcome prognosticators after supratentorial SICH in the Neurosurgery Department of a tertiary care hospital in the southeastern part of Bangladesh. Materials and Methods: This prospective interventional study included 183 patients with computerized tomography (CT) evidence of supratentorial SICH above 18 years of age from the Department of Neurosurgery of Chittagong Medical College Hospital between September 2021 and February 2023.The variables analyzed were age, sex, comorbidities, Glasgow coma scale (GCS) score on admission, radiological features, treatment modality and outcome at 90-day. Glasgow outcome scale (GOS) score was used to assess the outcome. GOS score 4-5 was considered good outcome and GOS score 1-3 was considered as poor outcome. Results: The mean age of the patients was 58.9±14.4 years and 52.5% were male. The 90-day mortality rate was 50.8% and 55.2% patients had poor outcomes. On bivariate analysis, higher age, comorbid CKD state, low GCS score, higher hematoma volume, midline shift, hydrocephalus and intraventricular hematoma (IVH) were associated with poor outcome. Independent predictors of poor outcome included a higher baseline age (OR: 1.07, 95% CI:1.02-1.11, p=0.002), lower GCS on admission (OR: 0.55, 95% CI: 0.39- 0.76, p<0.001), and medical management (OR = 30.56, 95% CI = 7.15-130.69, P <0.001). Conclusions: In conclusion, SICH is associated with high mortality and morbidity. Higher age, low GCS on admission and medical management independently predicted poor outcome in the present study. Patients with a lower age, higher GCS on admission and who were managed surgically were more likely to have a good outcome. Bang. J Neurosurgery 2024; 13(2): 96-103